The Strategy of Indonesia's Economic Diplomacy in Building Mandalika Special Economic Zone (2017-2021) - MASYHURI, AULIA RAHMATIN; Elvianti, Witri (Universitas Diponegoro, 2023)
In recent years, Indonesia has actively pursued economic diplomacy to enhance its international standing through trade, tourism, investment, and services (TTIS). This study focuses on analyzing Indonesia's economic diplomacy strategy in developing the Mandalika Special Economic Zone (SEZ) from 2017 to 2021. Employing a qualitative methodology involving data analysis and interviews, the research follows the four phases of economic diplomacy outlined by Kishan S. Rana, encompassing economic salesmanship, economic networking, image building, and regulatory management with resource mobilization. This aimed to unravel Indonesia's commitment to fostering tourism as a strategic sector, utilizing Mandalika SEZ to attract investments. Findings reveal that Indonesia has successfully navigated through the four phases, particularly emphasizing sports tourism in Mandalika and cultivating a conducive investment climate. The study underscores the academic importance by contributing insights into the intricacies of economic diplomacy, tourism development, and the role of non-state actors, exemplified by the ITDC serving as Mandalika's BUPP. This research bridges gaps in the literature, shedding light on the multifaceted nature of Indonesia's economic diplomacy and offering practical implications for policymakers and investors alike.